2014
DOI: 10.1111/asj.12235
|View full text |Cite
|
Sign up to set email alerts
|

Changes in vitamin A added to a fermented total mixed ration prepared with reed canarygrass (Phalaris arundinaceaL.)

Abstract: A fermented total mixed ration (TMR) was prepared by adding a vitamin premix containing vitamin A and enzyme to reed canarygrass roughage. The vitamin A levels were then determined after 30 days of fermentation at 20 or 30°C. The vitamin A contents had decreased in roughage fermented at both storage temperatures, and decreased further when an enzyme supplement was included. Because the majority of the added vitamin A was destroyed during fermentation and storage, the addition of vitamin A at the beginning of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…Lactobacillus strains need vitamins (Jaramillo et al, 2018) due to their limited ability to synthesize B vitamins (Gao et al, 2011). In the current study, we found that calcidiol, the metabolite of vitamin D3, was lower in FRU, but biocytin and acuminoside were greater in FRU and PEC compared to CON, indicating the protective roles of FRU and PEC in preventing the degradation of vitamins, as the ensiling procedure easily results in the loss of vitamins (Tagawa et al, 2014).…”
Section: Discussionsupporting
confidence: 45%
“…Lactobacillus strains need vitamins (Jaramillo et al, 2018) due to their limited ability to synthesize B vitamins (Gao et al, 2011). In the current study, we found that calcidiol, the metabolite of vitamin D3, was lower in FRU, but biocytin and acuminoside were greater in FRU and PEC compared to CON, indicating the protective roles of FRU and PEC in preventing the degradation of vitamins, as the ensiling procedure easily results in the loss of vitamins (Tagawa et al, 2014).…”
Section: Discussionsupporting
confidence: 45%